Modelling the Role of Temperature-Induced Environmental Noise on Phytoplankton Niche Dynamics - Sarker, Subrata; Mohammad, Deen; Nabil, Siam Ahmed; Kabir, Md. Alamgir (Frontiers in Marine Science, 2022)
Variability in physical and chemical processes in the marine ecosystem significantly influences the niche ecology of primary producers. However, studies are limited to understand the role of variability in environmental conditions on the niche dynamics of phytoplankton. Therefore, in this study we aimed to understand the role of environmental noise on the niche dynamics of phytoplankton species. This study performed numerical simulations by extending the classic Rosenzweig–MacArthur, predator–prey model for multiple species. We considered the characteristics timescale of seasonal sea surface temperature as environmental noise. Our study found that the oscillatory fluctuation of biomass, variation in carrying capacity, no competitive exclusion, and non-equilibrium state in periodic fluctuation of species biomass enables species to coexist in a noise-induced system. In addition, a high amplitude in species biomass fluctuation at a higher environmental noise was found as another potential coexistence mechanism. Our simulations found that the mean niche and niche width of species are significantly related to environmental noise (R2 = 0.93 and 0.98, respectively). We observed a shift in mean niche conditions of species with the change in environmental noise. Niche overlapping between species decreased significantly with the increase in environmental noise (R2 = 0.95). Our study will serve as a baseline to understand the complexity of phytoplankton niche dynamics in a variable environment.